Vaginal birth after cesarean section-The world trend and local experience in Taiwan - Hsiu-Ting Tsai; Chia-Hsun Wu (Elsevier, 2017)
Objective: The trend of increasing cesarean section rates had evoked worldwide attention. Many approaches were introduced to diminish cesarean section rates. Vaginal birth after cesarean section (VBAC) is a route of delivery with diverse agreements. In this study, we try to reveal the world trend in VBAC and our experience of a 10-year period in a medical center in northern Taiwan. Materials and methods: This is a retrospective study of all women who underwent elective repeat cesarean delivery or trial of labor after cesarean (TOLAC) following primary cesarean delivery by a general obstetrician-gynecologist in the Tamshui Branch of MacKay Memorial Hospital (Taipei, Taiwan) between 2006 and 2015. We excluded cases of preterm labor, two or more cesarean deliveries, and major maternal diseases. We compared the characteristics and outcomes between these groups. Results: We included 400 women with subsequent pregnancies who underwent elective repeat cesarean delivery or TOLAC during the study period. Among the study population, 112 women were excluded and 11 underwent repeat VBAC. A total of 204 (73.65%) cases underwent elective repeat cesarean delivery and 73 (26.35%) chose TOLAC. The rate of successful VBAC among the women who chose TOLAC was 84.93%. Conclusion: With respect to maternal and fetal safety, and success rates and adverse effects of VBAC, the results of this study are promising and compatible with the global data. It shows that a trial of VBAC can be offered to pregnant women without contraindications with high success rates.